Retrospective Study on Orthodontic Gingival Recession Correction Using Clear Aligners - Sorana Maria Bucur; Eugen Bud; Mioara Decusară; Cristian-Doru Olteanu (Medicina)
Background and Objectives: Our study aims to evaluate the effectiveness of ClearCorrect® clear aligners (The Straumann Group) in improving gingival recession, which developed following prior fixed orthodontic treatment. The specific objectives were to assess changes in recession severity in patients with orthodontic gingival recessions following aligner therapy and to determine whether the initial severity of recession influenced improvement rates across three categories—mild (RT1), moderate (RT2), and severe (RT3)—as defined by the Cairo classification. Materials and Methods: Fifty-six patients with gingival recession from previous orthodontic treatment received aligner therapy for seven to twelve months, focusing on 146 recession sites, primarily in the lower anterior region. Recession severity was classified and tracked as RT1, RT2, and RT3. Statistical analyses, including a Chi-square test, assessed improvement rates across these categories. Results: Among severe recessions (RT3), 52% showed no improvement, while 48% exhibited some improvement, with 16% improving to RT1. In the moderate group (RT2), 63% improved to RT1, and 16% resolved. The mild group (RT1) showed a 58% reduction in recession depth. Chi-square testing confirmed a statistically significant difference in improvement rates across the three groups (p = 1.44 × 10−7). Conclusions: Clear aligners may contribute to gingival recession improvement, particularly in mild and moderate cases (RT1 and RT2), though severe cases (RT3) show a more limited response.